Validation of two rapid diagnostic tests for visceral leishmaniasis in Kenya. - Jane Mbui; Monique Wasunna; Manica Balasegaram; Adrian Laussermayer; Rashid Juma; Simon Njoroge Njenga; George Kirigi; Mark Riongoita; Roberto de la Tour; Joke van Peteghem; Raymond Omollo; François Chappuis (Public Library of Science (PLoS), 2013)
BACKGROUND: Visceral leishmaniasis (VL) is a systemic parasitic disease that is fatal unless treated. In Kenya, national VL guidelines rely on microscopic examination of spleen aspirate to confirm diagnosis. As this procedure is invasive, it cannot be safely implemented in peripheral health structures, where non-invasive, accurate, easy to use diagnostic tests are needed. METHODOLOGY: We evaluated the sensitivity, specificity and predictive values of two rapid diagnostic tests (RDT), DiaMed IT LEISH and Signal-KA, among consecutive patients with clinical suspicion of VL in two treatment centres located in Baringo and North Pokot District, Rift Valley province, Kenya. Microscopic examination of spleen aspirate was the reference diagnostic standard. Patients were prospectively recruited between May 2010 and July 2011. PRINCIPAL FINDINGS: Of 251 eligible patients, 219 patients were analyzed, including 131 VL and 88 non-VL patients. The median age of VL patients was 16 years with predominance of males (66%). None of the tested VL patients were co-infected with HIV. Sensitivity and specificity of the DiaMed IT LEISH were 89.3% (95%CI: 82.7-94%) and 89.8% (95%CI: 81.5-95.2%), respectively. The Signal KA showed trends towards lower sensitivity (77.1%; 95%CI: 68.9-84%) and higher specificity (95.5%; 95%CI: 88.7-98.7%). Combining the tests did not improve the overall diagnostic performance, as all patients with a positive Signal KA were also positive with the DiaMed IT LEISH. CONCLUSION/SIGNIFICANCE: The DiaMed IT LEISH can be used to diagnose VL in Kenyan peripheral health facilities where microscopic examination of spleen aspirate or sophisticated serological techniques are not feasible. There is a crucial need for an improved RDT for VL diagnosis in East Africa.